PENGARUH LOKASI, NILAI PELANGGAN, DAN PERSAINGAN HARGA TERHADAP PENGGUNA JASA TRANSPORTASI PADA PT. PALAPA MEDAN - Hendra Jonathan Sibarani; Lestarida Febriana Simamora; Rovina Manihuruk; Januari Simarmata (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2021)
This study aims to determine the effect of location, customer value, and price competition on users of transportation services at PT. Palapa Medan with a population of 840 with a sample size of 89 people. The data collection techniques used in this study were questionnaires and interviews. The data analysis technique uses linear regression, classical assumption test, hypothesis test (t test, F test) and determinant coefficient, data processing in this study uses the SPSS (statistical package for the social sciences) software program version 20. Based on the partial test results (t-test) location (X1), and price competition (X3) have a positive and significant effect on users of transportation services (Y). For the results of the F test, it is obtained that the value of Fcount (7.893> 2.15) and sig F (0.000 <0.10), this means that simultaneously the variables of location, customer value and price competition have a significant effect on transportation service users.